Faktor-Faktor yang Berhubungan dengan Tingkat Kecerdasan Kognitif Anak di SDN Pasireurih 01 Kabupaten Bogor Tahun 2025 - Arini Kusmintarti; Deti Nurtika; Veronica Fary; Retno Ekawaty (INDO PUBLISHING, 2026)
Cognitive development in elementary school children is a fundamental foundation for their ability to think, learn, and achieve academic success in the future. Various factors such as nutritional status, gender, and participation in private tutoring are suspected to be associated with children’s cognitive intelligence levels. Objective: This study aims to determine the factors associated with the cognitive intelligence level of students at SDN Pasireurih 01 in 2025. Methods: This research employed a cross-sectional design with a quantitative approach. The study sample consisted of grade 3–4 students at SDN Pasireurih 01, selected using purposive sampling. Primary data were obtained through anthropometric measurements (nutritional status), respondent identity (gender, participation in private tutoring), and secondary data from the latest report card scores as indicators of cognitive intelligence. Data analysis was conducted using univariate and bivariate tests with a significance level of p<0.05. Results: The findings revealed that nutritional status was significantly associated with cognitive intelligence (p=0.002). Gender also showed a significant association (p=0.047), indicating differences in cognitive intelligence between male and female students. In addition, participation in private tutoring was significantly associated (p=0.017) with students’ cognitive intelligence levels. Conclusion: Nutritional status, gender, and participation in private tutoring were proven to be significantly associated with the cognitive intelligence level of students at SDN Pasireurih 01. Efforts to improve children’s nutritional status, attention to gender differences, and evaluation of the effectiveness of private tutoring are necessary to support cognitive development in elementary school children.